Effects of sports nutrition education on knowledge, attitude and practice of sports nutrition and nutritional status among elite male athletes in Malaysia - Mohd Elias, Siti Soraya (2017)
A proper knowledge, attitude and practice (KAP) of sports nutrition are associated with many positive outcomes for athletes including optimal health and performance. However, the level of sports nutrition knowledge of athletes has been a popular question for researchers in Malaysia because of the inadequate quantitative reporting in the form of a questionnaire test score. Thus, an education intervention program was carried out to evaluate the effects of the intervention in improving the KAP of sports nutrition and the nutritional status among elite male young adults team sports athletes in Malaysia. One hundred and five male team sports athletes aged between 18 to 32 years old participated in this study, 52 athletes were recruited in the treatment group (TG) while53 athletes were in the comparison group (CG). The TG received seven weeks education intervention program. The intervention activities consisted of booklet distribution and 60 to 90 minutes of lecture session with 30 minutes of group discussion on weekly basis. The booklet consist seven topics of basic sports nutrition. The lecture session and group discussion was conducted by the researcher with sports nutrition background. No intervention program was conducted for the CG as it served for the comparison purpose. A validated questionnaire on KAP of sports nutrition was used in this study. Three-day food records, three-day physical activity records, anthropometric measurement (bodyweight, height) and body composition assessment (seven sites skin folds) were used to measure athletes nutritional status that consist of dietary intake, energy balance and body composition status Looking at within groups effect, results show significant interaction between groups and time with the TG showing increments in the KAP scores while the CG showing reduction in KAP scores over the two time period. For dietary intake, the percentage of carbohydrate intake significantly decreased from 55% to 53% although the total carbohydrate intake in gram showed increment at post-test. This indicates the improvement in total energy intake at post-test in the TG is from the consumption of high protein foods and fat foods in place of carbohydrate rich foods. The percentage of protein and fat intake were significantly increased and meet the recommendation for total energy requirement with 19% of total protein and 30% of total fat. For energy balance, the TG showed significant increased at post-test by the reduction of negative energy balance during training days (-5 ± 628) and manage to achieve positive energy balance at rest day (188 ± 553). Meanwhile, no significant difference were found inthe parameter of anthropometric measures, while there was significant difference in body fat mass. The mean body fat mass showed significant increased in both TG(60.13 ± 5.34) and CG (67.97 ± 12.25) at post-test. For between groups effect, the main effect comparing two groups with the TG receiving an intervention program while the CG did not receive any intervention was significant (p<.05), suggesting there was differences between the two groups and the intervention program lead to positive effect in terms of the improvement in the KAP scores of the TG. There was a significant improvement in the adjusted mean score of knowledge on sports nutrition in the TG at post-test, the mean score of knowledge was significantly higher in the TG (20.04 ± 1.72) compared to the CG(13.68 ± 2.16). For attitude on sports nutrition, the mean score was significantly higher in the TG (64.04 ±5.52) as compared to the CG (55.17 ± 2.77) at post-test. Meanwhile for practice on sports nutrition the mean score at post-test in the TG (35.67 ± 3.53) was significantly higher as compared to the mean score in the CG (29.28 ± 4.84). For other variables, there were significant differences in the mean for total carbohydrate intake in g/kg body weight (5.82 ± 1.24 vs 4.12 ± 0.57), total protein intake (139.14 ± 22.22 vs141.34 ± 41.40) and total fat intake (94.03 ± 19.80 vs 96.21 ± 26.76) in the TG as compared to the CG. Furthermore at post-test, the mean energy balance during training days in the TG (-5 ± 628) was significantly higher than the CG (-513 ± 398).As a conclusion, the sports nutrition education intervention increased the scores of sports nutrition KAP in the TG and this program showed improvement in athletes nutritional status in terms of total energy intake and energy balance. However, the intervention program did not help in improving the anthropometric and body composition status of the athletes. The findings of this study support the need for and the positive effects of sports nutrition education intervention program and is useful for future intervention programs in improving sports nutrition knowledge and application especially among athletes.